2019
DOI: 10.3390/v11010049
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Isolated from Oriental Medicinal Herbs Inactivate Zika Virus

Abstract: Zika virus (ZIKV) has been associated with serious health conditions, and an intense search to discover different ways to prevent and treat ZIKV infection is underway. Berberine and emodin possess several pharmacological properties and have been shown to be particularly effective against the entry and replication of several viruses. We show that emodin and berberine trigger a virucidal effect on ZIKV. When the virus was exposed to 160 µM of berberine, a reduction of 77.6% in the infectivity was observed; when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 56 publications
1
42
0
1
Order By: Relevance
“…Moreover, some compounds, such as lycorine, emodin, and procyanidin, have been proven to be effective in inhibiting flavivirus or HCV infections via different mechanisms (16)(17)(18)(19)(20). Our high-content screening assay design could identify compounds that inhibit JEV viral entry, translation, and RNA synthesis.…”
Section: Ouabain Blocks Jev Infectionmentioning
confidence: 99%
“…Moreover, some compounds, such as lycorine, emodin, and procyanidin, have been proven to be effective in inhibiting flavivirus or HCV infections via different mechanisms (16)(17)(18)(19)(20). Our high-content screening assay design could identify compounds that inhibit JEV viral entry, translation, and RNA synthesis.…”
Section: Ouabain Blocks Jev Infectionmentioning
confidence: 99%
“…In February 2016, the World Health Organization (WHO) declared ZIKV to be a Public Health Emergency of International Concern (PHEIC) [13]. Strategies of fighting ZIKV infection include the development of vaccines and the screening of antiviral agents that inhibit different stages of the viral life cycle [14]. Unfortunately, no approved antiviral ZIKV agents are currently available.…”
Section: Introductionmentioning
confidence: 99%
“…The development of plant-derived substances used as nutraceuticals and capable of inhibiting the infection of emerging viruses represents an attractive and eco-friendly strategy [ 41 ]. Indeed, several studies have shown that plants represent a promising source of antivirals against emerging viruses [ 17 , 18 , 19 , 22 , 23 , 24 , 30 , 42 , 43 ]. In this study, we showed for the first time that papaya fruit pulp inhibited the infection of A549 cells by the epidemic ZIKV without reducing cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Neither an effective treatment nor a vaccine is available for ZIKV. Given that several countries around the world are at risk of ZIKV outbreaks, it is still of high importance to develop antiviral strategies that include the use of nutraceuticals that can be used to prevent ZIKV infection [17][18][19][20][21]. Several polyphenol-rich extracts from Reunion Island have been reported to prevent ZIKV infection in vitro [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%